Intercollegiate Cooperation between Students of History Scientific Associations (1921–1969) – Basic Aspects of the Issue (Vade Nobiscum, tom XXI/2019: Studia z historii gospodarczej, kulturowej i społecznej, 2019)
First students of history scientific association appeared in Galicia in second half of the 19th century however cooperation between then began in 1921. It involved several fields. Some institutions coordinated that process in the past. The aim of the article is to approach history of them as well as other forms of intercollegiate cooperation between students of history scientific associations.